The Art of Goodbye: Putting Your Legal and Financial Affairs in Order - Brenda C. Williams (EDIS)
Making final legal and financial decisions can often be an uncomfortable and complex process. This 4-page document from The Art of Goodbye series is designed to help you consider your specific circumstances and gather the information you will need when talking with professionals who will work to carry out your wishes. Written by Brenda C. Williams, and published by the UF/IFAS Department of Family, Youth and Community Sciences, January 2018. http://edis.ifas.ufl.edu/fy1472